Leonard Bernstein a New York - Čenský, Petr (Lidé města, 2006)
As a composer, Leonard Bernstein revived worldwide interest in works of the Austro-Hungarian composer (as well as a conductor) Gustav Mahler (1860–1911). Bernstein felt to be strongly related to him, even considered himself as his reincarnation. However, if we examine closely both these creators and their work, we realize how they differ in one significant aspect of world perception: Mahler was a composer of nature and countryside, whereas Bernstein composed music about a city. Both of them spent their lives in larger and large cities: Mahler spent his childhood in Jihlava and later worked as a composer, among other cities, in Prague, Budapest, Hamburg, Vienna, and finally in New York. Bernstein was born near Boston, but then chose New York as his home. Yet, their view of a city was dramatically different. In one of his letters Mahler writes: “When I came to Zahlendorf, that is the name of this place, and searched for a path through pines and spruces totally covered with snow, everything was quite rural, nice church joyfully glittering in winter sunrays, at that moment I felt elated and I saw how one suddenly becomes free and full of joy when he returns from unnatural and restless babble of a big city to the quiet house of nature”. While Bernstein says about New York: “This city got me in its grips. No wonder I compose music about it again and again. (…) Everything is so dramatic, so full of life”.